TNF-α exacerbates calcium influx via voltage-gated calcium channels in breast cancer cells: a nanoscale multimodal AFM study - Wang, Zhongwei; Xu, Qianhui; Zhang, Huaiwei; Feng, Rongrong; Chen, Junmei; Wei, Jinsong; Zhong, Haijian; Zhao, Weidong (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTumor necrosis factor-α (TNF-α) is considered a potential therapeutic strategy for cancers, as it exacerbates calcium influx through voltage-gated calcium channels (VGCCs), thereby inducing apoptosis. However, the mechanisms underlying TNF-α's effects at the single-molecule level remain unclear.MethodsThis study employed multiple modes of Atomic Force Microscopy (AFM) to investigate the impact of TNF-α on breast cancer cells. The measurements were performed with nanometer spatial resolution, picoNewton force sensitivity, picoAmpere current precision, and 0.1 mV surface potential accuracy.ResultsThe results revealed that TNF-α treatment significantly increased the density and aggregation of VGCCs on the cell membrane while enhancing their channel activity. Concurrently, the electrical conductivity and surface potential of the membrane were elevated, collectively promoting exacerbated calcium influx.DiscussionThese findings elucidate the mechanisms by which TNF-α modulates VGCC distribution and electrophysiological properties to amplify calcium signaling, ultimately triggering apoptosis. This study provides unprecedented insights into TNF-α-induced calcium dysregulation in cancer cells at the single-molecule level, offering a novel approach for investigating apoptosis and advancing targeted therapies for breast cancer and other malignancies.